2010
DOI: 10.1002/pbc.22422
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease preceding haemophagocytic lymphohistiocytosis: Challenges for developing world practitioners

Abstract: Kawasaki disease (KD) is a recognised precipitant of haemophagocytic lymphohistiocytosis (HLH). Although KD has been previously described in the developing world, there are no reported cases of KD preceding HLH. We report a case of a child with a persistent rash and unremitting fever consistent with the diagnosis of KD, who was found to have HLH, after intravenous gamma globulin failed to produce a clinical response. The diagnosis was made using the revised diagnostic criteria for HLH from the Histiocyte Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…High serum ferritin levels are a feature of HLH. HLH has been described in association with KD in several reports (16)(17)(18)(19)(20)(21). Similarities between the two conditions, and reports of the presence of features of both HLH and KD in some patients may also suggest that the initial inflammatory response manifesting as KD might progress to HLH if untreated.…”
Section: Discussionmentioning
confidence: 75%
“…High serum ferritin levels are a feature of HLH. HLH has been described in association with KD in several reports (16)(17)(18)(19)(20)(21). Similarities between the two conditions, and reports of the presence of features of both HLH and KD in some patients may also suggest that the initial inflammatory response manifesting as KD might progress to HLH if untreated.…”
Section: Discussionmentioning
confidence: 75%
“…In short, HLH was interpreted as secondary disease induced by KD. 4,5,[7][8][9][10] In contrast, Titze et al 6 reported on the patient who had either HLH secondary to KD, or both as a result of a yet unknown common triggering mechanism. In fact, a number of immunological alterations reported in KD, most of which overlap with HLH, suggest a similar pathophysiology for these conditions, that is, serum levels of IL-6, IL-8, TNF-a, and sIL-2R are found to be elevated in both HLH and KD.…”
Section: Discussionmentioning
confidence: 87%
“…3 Thus, HLH and KD seem to share the similar pathogenesis and several cases with KD preceding HLH have been reported. [4][5][6][7][8][9][10] We here firstly report a pediatric case of HLH associated with Epstein-Barr virus (EBV-HLH), which fulfilled the diagnostic criteria of KD including the typical complication of CAL, and which also demonstrated increased serum levels of proinflammatory cytokines previously reported in both HLH and KD.…”
mentioning
confidence: 92%
“…Hemophagocytic syndromes were also described as a complication of several other autoimmune disorders, e.g. systemic lupus erythematosus (SLE), juvenile dermatomyositis or Kawasaki disease [47][48][49][50]. Unfortunately, numerous cases of MAS and HLH remain undiagnosed and appropriate treatment is not applied.…”
Section: Discussionmentioning
confidence: 99%